Current perspectives on obesity and skeletal muscle contractile function in older adults - Straight, Chad R. (J Appl Physiol (1985), 2021)
Obesity has become one of the most pressing public health issues of the 21st century and currently affects a substantial proportion of the older adult population. Although the cardiometabolic complications are well documented, research from the past 20 years has drawn attention to the detrimental effects of obesity on physical performance in older adults. Obesity-related declines in physical performance are due, in part, to compromised muscle strength and power. Recent evidence suggests there are a number of mechanisms potentially underlying reduced whole muscle function, including alterations in myofilament protein function and cellular contractile properties, and these may be related to morphological adaptations, such as shifts in fiber type composition and increased intramyocellular lipid content within skeletal muscle. To date, even less research has focused on how exercise and weight loss interventions for obese older adults affect these mechanisms. In light of this work, we provide an update on the current knowledge related to obesity and skeletal muscle contractile function and highlight a number of questions to address potential etiologic mechanisms as well as intervention strategies, which may help advance our understanding of how physical performance can be improved among obese older adults.